Accelerating rural creative economy: Youth digital entrepreneurship empowerment in Timpuseng Village - Rahman, Karlina Ghazalah; Ridwan, Ridwan; Rasyid, Asriadi; Wirawan, Raden; Said, Muh; Hamzah, Mukhtar (Community Empowerment, 2025)
Timpuseng Village faces youth urbanization challenges due to limited local employment opportunities, despite its significant economic potential. This community service program aims to foster youth entrepreneurship by strengthening digital literacy and optimizing e-commerce platforms. The implementation methods included participatory training, technology integration, intensive two-week monitoring, and the establishment of a youth entrepreneur community. Results indicated a significant 102.22% increase in participants' knowledge scores (from an average of 41.8 to 84.07). Additionally, 100% of participants successfully activated digital business accounts, with 83.3% recording interactions or transactions within the first 14 days. This program demonstrates that digital literacy effectively transforms village youth from job seekers into independent local creative economy drivers.